(3eHGOF GdEbJUGO (B:s (3GdJMdjd Gdcdj (B/s - (3YQjbGJ, MQHj eMeO eQSjs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2006)
(3eONd Gdi Yde GdEbJUGO(B- (3MSGHGJ GdONd Gdbhej(B- (3fXQjGJ GdESJgdGc(B- (3JNWjW GdESJKeGQ(B- (3fXQjI GdEONGQ(B- (3GdHWGdI(B- (3GdJVNe GdSjGSI GdeGdjI(B- (3GdfbhO(B- (3GdeUGQa(B- (3GdJLGQI GdNGQLjI(B- (3GdJfejI GdEbJUGOjI hGdfeh GdEbJUGOj(B- (3GdJNWjW GdEbJUGOj(B- (3GdJcGed GdEbJUGOj(B.s
Keywords: (3GdEbJUGOs; (3GdEbJUGO Gdcdjs; (3GdEbJUGO GdeGdjs